Doppelperfekt und Plusquamperfekt im Hoch- und Oberrheinalemannischen Südwestdeutschlands - Leonhard, Jens (Linguistik online, 2019)
In this paper I discuss the tenses Doppelperfekt and Plusquamperfekt in spoken High Alemannic and Upper-Rhine Alemannic in south-western Germany with a usage-based approach and a statistical evaluation. I show that both Doppelperfekt and Plusquamperfekt have a past perfect meaning, i. e. they refer to a point of time in the past placed before another point of time in the past. Furthermore, I account for a language change in the timespan from 1974 to 2013 in which the Plusquamperfekt becomes more frequent in relation to the Doppelperfekt. Additionally, I show that speakers use the Doppelperfekt in the old data with both auxiliaries (sein and haben), and in the new data only with the auxiliary haben. In contrast to this, the Plusquamperfekt is used in the old data only with the auxiliary sein, and in the new data with both auxiliaries sein and haben. These results could lead to the conclusion that the Doppelperfekt und Plusquamperfekt cannot exist simultaneously in an equivalent manner.